Cultural history of chemistry : volumes 1-6 - Peter J T Morris; Alan Rocke (London: Bloomsburry, 2021)
"The first detailed and authoritative survey of chemistry and its central role in society over the last 5000 years. From prehistoric metal extraction to medieval alchemy to modern industry, chemistry has been central to our understanding and use of the physical world as well as to trade, warfare and medicine. In its turn, chemistry has been shaped by changing technologies, institutions and cultural beliefs. A Cultural History of Chemistry presents the first detailed and authoritative survey from antiquity to today, focusing on the West but integrating key developments in Egypt, Mesopotamia, and the Arabic-Islamic and Byzantine empires"--
v. 1. A cultural history of chemistry in antiq -- v. 2. A cultural history of chemistry in the m -- v. 3. A cultural history of chemistry in the e -- v. 4. A cultural history of chemistry in the e -- v. 5. A cultural history of chemistry in the n -- v. 6. A cultural history of chemistry in the m